Plastic Surgery and Music: Examining Plastic Surgery References in Hit Songs. Issue 6 (15th June 2021) - Castro, Ruben; Tsutsumi, Kotaro; Sayadi, Jamasb J.; Hu, James; Vyas, Raj M.; Sayadi, Lohrasb R.
SUMMARY: The purpose of this study was to assess the frequency by which plastic surgery-related terms have been included in the lyrics of Western music hits from the 1970s to the present day as a proxy for estimating the cultural impact of plastic surgery. A list of the Billboard Year-End Hot 100 songs from 1968 to 2019 and the Billboard Year-End Hot R&B/Hip-Hop songs from 1970 to 2019 was obtained for a combined total of 8550 songs. Lyrics for each song were extracted via a web-scraping system, and a database of plastic surgery-related terms was developed by our team. Each term was then queried amongst the compiled lyrics data sets, and the total frequency of plastic surgery-related terms per year and per decade was determined. Each term was also examined in its context of usage to validate its relevance to plastic surgery and determine its connotation through sentiment analysis. The frequency of plastic surgery-related terms referenced in the Billboard Year-End Hot 100 and Billboard Year-End Hot R&B/Hip-Hop charts has increased 15-fold from the 1970s (n = 1 song) to 2010s (n = 15 songs). The terms most often mentioned included "doctor, " "silicone, " "plastic, " "surgery, " "nip-tuck, " and "lipo." Artists who most frequently used plastic surgery-related terms were Kanye West, 2 Chainz, and Nicki Minaj. The current study is the first to evaluate trends in plastic surgery references in music formally. In turn, this study helps further our understanding of the interplay between plastic surgery and popular culture.